An innovative design for cardiopulmonary resuscitation manikins based on a human-like thorax and embedded flow sensors. (March 2017) - Thielen, Mark; Joshi, Rohan; Delbressine, Frank; Bambang Oetomo, Sidarto; Feijs, Loe
Cardiopulmonary resuscitation manikins are used for training personnel in performing cardiopulmonary resuscitation. State-of-the-art cardiopulmonary resuscitation manikins are still anatomically and physiologically low-fidelity designs. The aim of this research was to design a manikin that offers high anatomical and physiological fidelity and has a cardiac and respiratory system along with integrated flow sensors to monitor cardiac output and air displacement in response to cardiopulmonary resuscitation. This manikin was designed in accordance with anatomical dimensions using a polyoxymethylene rib cage connected to a vertebral column from an anatomical female model. The respiratory system was composed of silicon-coated memory foam mimicking lungs, a polyvinylchloride bronchus and a latex trachea. The cardiovascular system was composed of two sets of latex tubing representing the pulmonary and aortic arteries which were connected to latex balloons mimicking the ventricles and lumped abdominal volumes, respectively. These balloons were filled with Life/form simulation blood and placed inside polyether foam. The respiratory and cardiovascular systems were equipped with flow sensors to gather data in response to chest compressions. Three non-medical professionals performed chest compressions on this manikin yielding data corresponding to force–displacement while the flow sensors provided feedback. The force–displacement tests on this manikin show a desirable nonlinear behaviour mimicking chest compressions during cardiopulmonary resuscitation in humans. In addition, the flow sensors provide valuable data on the internal effects of cardiopulmonary resuscitation. In conclusion, scientifically designed and anatomically high-fidelity designs of cardiopulmonary resuscitation manikins that embed flow sensors can improve physiological fidelity and provide useful feedback data.